The coming of age of musculoskeletal tissue engineering and regeneration - Tuan, Rocky S. (Nat Rev Rheumatol, 2013)
Tissue engineering and regenerative medicine have advanced rapidly towards the development of therapeutic solutions for musculoskeletal disorders. In 2012, breakthroughs have been made in the guidance of adult stem cell homing, the tissue regenerative activity of stem-cell-derived extracellular matrix has been tested, and novel, mechanically superior biomaterials have been fabricated.